2013
DOI: 10.1002/hep.26608
|View full text |Cite
|
Sign up to set email alerts
|

Organized proteomic heterogeneity in colorectal cancer liver metastases and implications for therapies

Abstract: Tumor heterogeneity is a major obstacle for developing effective anticancer treatments. Recent studies have pointed to large stochastic genetic heterogeneity within cancer lesions, where no pattern seems to exist that would enable a more structured targeted therapy approach. Because to date no similar information is available at the protein (phenotype) level, we employed matrix assisted laser desorption ionization (MALDI) image-guided proteomics and explored the heterogeneity of extracellular and membrane subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…The heterogeneity of the expression level of an oncogenic protein, as well as its post-translationally modified isoforms, may have implications for the progression of tumour development, affecting tumour promoting factors such as angiogenesis, the epithelial to mesenchymal transition, resistance to chemotherapy and likelihood of metastasis [11]. Furthermore, identifying heterogeneous expression of protein drug targets may be a useful method of stratifying patients by the likelihood of response to particular therapeutic interventions [12,13]. The significance of heterogeneous subpopulations can be realised by correlating the proteomic data to therapeutic and other clinically relevant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of the expression level of an oncogenic protein, as well as its post-translationally modified isoforms, may have implications for the progression of tumour development, affecting tumour promoting factors such as angiogenesis, the epithelial to mesenchymal transition, resistance to chemotherapy and likelihood of metastasis [11]. Furthermore, identifying heterogeneous expression of protein drug targets may be a useful method of stratifying patients by the likelihood of response to particular therapeutic interventions [12,13]. The significance of heterogeneous subpopulations can be realised by correlating the proteomic data to therapeutic and other clinically relevant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…CTC (circulation tumor cells) may be associated with recurrence of liver cancer. Researchers believe that the liver cancer stem cells do exist, and may be the target of target therapy of liver cancer [5].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor heterogeneity is a major obstacle for developing effective anti-cancer treatments. Recent studies suggested large stochastic genetic heterogeneity within cancer lesions, where no pattern seems to exist that would enable a more structured targeted therapy approach [5]. Efforts to develop more effective drugs for therapy on critical ill patients of advanced liver cancer have been intensified.…”
Section: Introductionmentioning
confidence: 99%
“…active glucose metabolism), in the ulcer floor (stress response) and in the invasive front (apoptosis). We have recently utilized MALDI-imaging to guide proteomics for analysis of defined regions of interest in human colorectal carcinoma liver metastases (CRC-LM) [48]. Namely, MALDIimaging allowed the identification of a certain pattern of peptide distribution in CRC-LM, subdividing the lesion in several zones.…”
Section: Paradigm-shift From Emerging Proteomic Studiesmentioning
confidence: 99%
“…This shift from targeting pure function towards inducing massive damage will certainly profit from new proteomic findings showing that tumor heterogeneity can be targeted in a meaningful fashion. We have in our study [48] named several clinically approved antibodies and quantified their distribution in CRC-LM. Based on this information, it should be conceivable to combine several targeted treatments and test this in reliable preclinical models.…”
Section: Consequences For Targeted Therapiesmentioning
confidence: 99%